2019
DOI: 10.1146/annurev-earth-053018-060457
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Early Warning: Advances, Scientific Challenges, and Societal Needs

Abstract: Earthquake early warning (EEW) is the delivery of ground shaking alerts or warnings. It is distinguished from earthquake prediction in that the earthquake has nucleated to provide detectable ground motion when an EEW is issued. Here we review progress in the field in the last 10 years. We begin with EEW users, synthesizing what we now know about who uses EEW and what information they need and can digest. We summarize the approaches to EEW and gather information about currently existing EEW systems implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
229
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(263 citation statements)
references
References 103 publications
1
229
0
Order By: Relevance
“…Whether earthquake complexity reflects underlying organization or randomness is a fundamental issue in earthquake physics and predictability. Recent work has suggested that organization in earthquake complexity permits a sense of determinism whereby observations made in a short period of time at the beginning of an earthquake may be used to infer the overall event size and style (Olson & Allen, 2005;Melgar & Hayes, 2017;Goldberg et al, 2018;Allen & Melgar, 2019). Previous studies have found that early P wave arrivals carry information about the overall earthquake size (Iio, 1995;Beroza & Ellsworth, 1996;Allen & Kanamori, 2003;Olson & Allen, 2005), but such correlations bear large uncertainties that necessitate additional information, such as attenuation parameters, in order to conduct meaningful early magnitude estimation (Wu et al, 2006;Colombelli et al, 2014;Noda & Ellsworth, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Whether earthquake complexity reflects underlying organization or randomness is a fundamental issue in earthquake physics and predictability. Recent work has suggested that organization in earthquake complexity permits a sense of determinism whereby observations made in a short period of time at the beginning of an earthquake may be used to infer the overall event size and style (Olson & Allen, 2005;Melgar & Hayes, 2017;Goldberg et al, 2018;Allen & Melgar, 2019). Previous studies have found that early P wave arrivals carry information about the overall earthquake size (Iio, 1995;Beroza & Ellsworth, 1996;Allen & Kanamori, 2003;Olson & Allen, 2005), but such correlations bear large uncertainties that necessitate additional information, such as attenuation parameters, in order to conduct meaningful early magnitude estimation (Wu et al, 2006;Colombelli et al, 2014;Noda & Ellsworth, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Earthquake early warning systems (EEWS) are essential tools for disaster risk reduction. Current systems detect earthquakes and estimate their source parameters based on the initial P-waves, which precede the most damaging shaking carried by S-waves (Allen & Melgar, 2019). However, the promptness of current systems is limited by the fact that P-waves, the information carrier, are less than twice as fast as S-waves, the damage carrier: earthquake detection and alert take a substantial portion of the travel time of the hazard, especially if seismometers are not located near the epicenter.…”
Section: Introductionmentioning
confidence: 99%
“…We can also use the focal mechanism of the mainshock to calculate the static Coulomb stress changes [24][25][26] for examining the earthquake triggering theory of the aftershocks [27][28][29] . Furthermore, the timely derived source focal mechanism can provide signi cant additions such as fault orientation and slipping mode to the point-source ground motion prediction model that is currently in practice [30][31][32] and thus has the potential to help improve the predicted ground shakings for early warning purpose. The immediate determination of the source focal mechanism is therefore of great importance to monitor and assess seismic hazards.…”
Section: Introductionmentioning
confidence: 99%